Identification of Malaysian Lemon Myrtle (Backhousia citriodora F. Muell) chemical constituents responsible for insecticidal activity using GC-MC-based metabolomics - Garba, Jamila (2016)
Anti-feedant and larvicidal activities of the essential oil, hexane, ethyl acetate and methanol extracts of Backhousia citriodora (grown in Malaysia) were studied using leaf disc no-choice and leaf dip methods respectively, against second instar larvae of S. litura and C. binotalis. Backhousia citriodora, commonly known as lemon myrtle, is a native Australian plant which belongs to the Myrtaceae family. Lemon myrtle steamdistilled essential oil has been reported to exhibit effective repellent properties against mosquitoes (domestic insects); making lemon myrtle a valuable exploratory source of novel insecticides for the management of agricultural insects. Spodoptera litura and Crocidolomia binotalis are dangerous agricultural insects. While S. litura is already resistant to many classes of synthetic insecticides, insecticides used in controlling C. binotalis are lethal to living organisms and also contaminate the environment. Therefore this study was carried out to investigate the insecticidal potential of lemon myrtle plant extracts against S. litura and C. binotalis. Lemon myrtle hexane extract showed maximum larvicidal activity of 100% at 5.0% (w/v) concentration with a lethal concentration (LC50) value of 1.8% (w/v), against C. binotalis. At 5.0% (w/v) concentration, the hexane extract killed 80.0 ± 2.9% of second instar S. litura larvae after 72 hours. The active hexane extract was subjected to Vacuum Liquid Chromatography (VLC) which afforded four major fractions namely LM1, LM4, LM5 and LM7. When tested against C. binotalis, fraction LM4 displayed maximum larvicidal activity of 100%, at a concentration of 1.4% (w/v) with an LC50 of 0.8% (w/v). At the same concentration, the fraction LM4 also completely inhibited the feeding activity of C. binotalis larvae, thus indicating good anti-feedant properties. Gas Chromatography-Mass Spectrometry (GC-MS) and Orthogonal Partial Least Squares (OPLS) were employed to investigate the chemical constituents of the different fractions. The compounds responsible for the insecticidal activity of lemon myrtle were identified as epoxy-linalool oxide, isopropyl 4-methyl-3-methylene-4-pentenoate, neric acid and citral. The results of this study indicated that lemon myrtle leaf extract, particularly the hexane extract, possesses remarkable insecticidal properties and could therefore, serve as a viable source for the development of a safer and efficient insecticide for crop protection.